2016
DOI: 10.1177/1940082916667139
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Giant South American Turtle (Podocnemis expansa) nesting habitat to climate-change-induced alterations to fluvial cycles

Abstract: A change in seasonal flooding cycles in the Amazon may negatively impact nesting success of the Giant South American Turtle (Podocnemis expansa). Our aim was to devise a technique that could be replicated in the entire Amazon basin, for monitoring alterations in fluvial cycles and their effects on turtle nest mortality. We mapped the spatial distribution and height of P. expansa nests and tested the effects of different inundation scenarios within the Trombetas River Biological Reserve, Para state, Brazil. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 55 publications
1
44
0
Order By: Relevance
“…Páez and Bock () suggested the utilization of black plastic as a tactic to decrease the incubation period and consequently increase egg survivorship. Shortening the incubation period could be an important management tool in areas where the sudden rise of the water level is a common event and the main cause of egg mortality (Hildebrand et al , Eisemberg et al ). Our results suggested that black plastic did accelerate embryonic development, reducing average incubation period by 3 days.…”
Section: Discussionmentioning
confidence: 99%
“…Páez and Bock () suggested the utilization of black plastic as a tactic to decrease the incubation period and consequently increase egg survivorship. Shortening the incubation period could be an important management tool in areas where the sudden rise of the water level is a common event and the main cause of egg mortality (Hildebrand et al , Eisemberg et al ). Our results suggested that black plastic did accelerate embryonic development, reducing average incubation period by 3 days.…”
Section: Discussionmentioning
confidence: 99%
“…Climate change can also affect fecundity by changing the accessibility of suitable nesting substrates. Sand bank availability in the Trombetas Reserve in Brazil during the dry season has declined over 40 years, and Arrau turtle (Podocnemis expansa) populations may be declining in part due to the reduction of this habitat as the length of the dry season continues to shorten [77]. Likewise, little has been published linking climatic conditions with survivorship in chelonians.…”
Section: Populationsmentioning
confidence: 99%
“…Nine of the 46 chelonian species (19.6%) studied by Böhm et al [98] were considered to be highly vulnerable to climate change, and climate vulnerability for all reptilian species considered was highest in portions of the Amazon basin and northwestern South America, southwestern USA, and parts of southeastern Asia. For example, changes in the hydrology of the Amazon basin, leading to shorter dry periods, could be detrimental to the reproductive success of the Arrau turtle (Podocnemis expansa), as this species nests along alluvial riverbanks [77].…”
Section: Populationsmentioning
confidence: 99%
“…Like many tropical species Amazonian freshwater turtles are threatened by deforestation (Fagundes et al 2018), climate change (Eisemberg et al 2016), and unsustainable exploitation (Rachmansah et al 2020;Smith 1979). Precautionary estimates suggest that populations of the once abundant Yellow-spotted river turtle (Podocnemis unifilis) may experience severe (≥50%) and rapid (<50 years) future losses across 60% (5.3 M km 2 ) of the pan-Amazonian range (Norris et al 2019).…”
Section: Introductionmentioning
confidence: 99%